(untitled) (Interdisciplinary Journal of Nursing and Health, 2023)
Wound care used to be more of an art than a science, but thanks to contributions from different disciplines, wound care is now firmly based on science and clinical evidence using a holistic view of the patient. This means not only focusing on the specific wound that needs to be treated, but also trying to observe and understand the patient’s overall health. Such an approach requires a range of skills from medicine to physiology, psychology, clinical engineering and patient care. The management of the patient with skin lesions, a subject that is often underestimated, requires targeted and timely interventions through the creation of specialised and multidisciplinary teams. These teams can accompany the person throughout their treatment journey, ensuring effectiveness of treatment and equanimity of access to care.